El tiempo satírico (Minerva, 2019)
It is said traditionally that the present is the temporal axis common to the satiric genre. To justify this assertion, one can usually draw on arguments like the characteristical satiric tendency to use the narrative first person. In this paper, having exposed the different theoretical perspectives about this theme, it can be concluded that the satiric present is an intemporal literary creation oposed to the also intemporal literary past, represented by the concept of mores maiorum.